Code-Switching Found in Maudy Ayunda’s Podcast "Dating Tips: Jangan Dikit-Dikit Putus" - Zakia Viadinis Sarofa; Elshadai Gabriella; Veronika Marpaung; Wins Ardho Wardhana; Athiya Minarahmah; Syla Apriliani (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2026)
Code-switching are a prominent sociolinguistic phenomenon in bilingual and multilingual communities, yet its use in long-form digital communication such as podcasts remains underexplored. Previous studies examining Maudy Ayunda’s bilingual practices in interviews, music-related content, and educational videos have shown variations in the dominance of intersentential and intrasentential switching depending on media format and communicative goals, but none have systematically analyzed her linguistic behavior in podcast interactions. Addressing this gap, the present study investigates the types, frequency, and communicative functions of code-switching in Maudy Ayunda’s podcast episode “Dating Tips: Jangan Dikit-Dikit Putus.” Employing a qualitative descriptive approach, the study uses Poplack’s (1980) typology to identify occurrences of intersentential, intrasentential, and tag-switching within the transcribed data. The findings reveal that intrasentential switching appears most frequently, functioning to clarify concepts, express stance, and maintain conversational flow, while intersentential switching is used to emphasize key points or introduce topic shifts. Tag-switching occurs less frequently but serves important pragmatic purposes such as softening statements and establishing rapport. Overall, the results demonstrate that Maudy’s code-switching is strategic, context-sensitive, and socially meaningful, reflecting her bilingual identity and her intent to connect with listeners who share similar linguistic repertoires. This study contributes to the broader understanding of bilingual communication in Indonesian digital media by providing a detailed account of code-switching patterns in an unscripted podcast setting.